Eat, poop, die : how animals make our world - Roman, Joe, 1963- (Little, Brown Spark, 2023)
"Reveals how ecosystems are sculpted and sustained by animals eating, pooping, and dying--and how these fundamental functions could help save us from climate catastrophe."--Dust jacket